Analysis of Problems in The Science Learning Process at Elementary Schools - Agus Roniel Kogoya; Asep Saefulloh; Yoga Adi Pratama (CV. Global Cendekia Inti, 2026)
This study aims to examine the problems encountered in the science learning process among fifth-grade elementary school students in West Java within the context of 21st-century education, which emphasizes critical thinking, scientific attitudes, and practice-based learning experiences. The study employed a qualitative descriptive approach using closed-ended questionnaires distributed to students and in-depth interviews with science teachers and homeroom teachers. The findings reveal that science learning continues to face several interconnected challenges, particularly related to teachers’ pedagogical competence and the utilization of instructional media. Low student participation and learning motivation were strongly influenced by the dominance of teacher-centered conventional teaching methods, resulting in limited opportunities for students to engage in exploratory and contextual learning experiences. In addition, available learning facilities had not been optimally utilized in experimental and hands-on learning activities. The study concludes that strengthening teachers’ competencies in developing active, contextual, and experience-based science instruction is urgently needed. Therefore, continuous professional development programs focusing on innovative science teaching strategies and effective utilization of learning media are essential in elementary education.